2015
DOI: 10.1016/j.ygeno.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of chloroplast genomes in green plants

Abstract: Chloroplasts are essential organelles, in which genes have widely been used in the phylogenetic analysis of green plants. Here, we took advantage of the breadth of plastid genomes (cpDNAs) sequenced species to investigate their dynamic changes. Our study showed that gene rearrangements occurred more frequently in the cpDNAs of green algae than in land plants. Phylogenetic trees were generated using 55 conserved protein-coding genes including 33 genes for photosynthesis, 16 ribosomal protein genes and 6 other g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
67
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 49 publications
(68 reference statements)
11
67
1
Order By: Relevance
“…There were notable exceptions however, particularly in the rps2 , rpl32 , rps19 , rps7 , accD , rpl2 , rpl23 , clpP , ndhB , ndhA , and rps12 genes, which showed sequence homologies of only between 60% and 79%. These findings are consistent with the literature view that most photosynthesis-related genes are conserved to a higher level than ribosomal genes, with chloroplast genomes showing far higher degrees of conservation than the nuclear and mitochondrial genomes (Xu et al , 2015). Despite the high level of variation in the rps12 gene, loss of rps12 function might be predicted to lead to impaired chloroplast translation (Ramundo et al , 2013).…”
Section: Discussionsupporting
confidence: 92%
“…There were notable exceptions however, particularly in the rps2 , rpl32 , rps19 , rps7 , accD , rpl2 , rpl23 , clpP , ndhB , ndhA , and rps12 genes, which showed sequence homologies of only between 60% and 79%. These findings are consistent with the literature view that most photosynthesis-related genes are conserved to a higher level than ribosomal genes, with chloroplast genomes showing far higher degrees of conservation than the nuclear and mitochondrial genomes (Xu et al , 2015). Despite the high level of variation in the rps12 gene, loss of rps12 function might be predicted to lead to impaired chloroplast translation (Ramundo et al , 2013).…”
Section: Discussionsupporting
confidence: 92%
“…However, some angiosperm lineages may have extreme variations in their genome size, for instance, Cutinus (Cytinaceae) chloroplast genome is around 20 kb, while Chlorophyta (i.e., Floydiella, Chaetopeltidaceae) chloroplast genomes have been reported to host an unexpected large size of 520 kb [6]. The size of cpDNA has been compared within many clades [7,8], and many factors could explain these chloroplast genome size variation, like (a) variations of intergenic regions, intron lengths, etc. [9,10];(b) IR region variation [5,11]; (c) gene loss [12].…”
Section: Introductionmentioning
confidence: 99%
“…For the IR variation, the lengths of IRs are likely to be expanded, contracted or to be completely lost. The IR analyses of all green plants showed that short IRs are frequently found in Bryophyta followed by Chlorophyta, the lowest among Polypodiopsida followed by basal Magnoliophyta, Magnoliidae, Commelinids [11], and in Papilionoideae, Pinaceae, cupressophytes, IRs are nearly lost or missing [8,13,14]. Regarding the gene variation, the cpDNA of green plants are normally conserved, but gene losses are widely seen especially in parasitic plants such as Cuscuta and Epifagus, which have partially or completely lost the photosynthetic ability [15].…”
Section: Introductionmentioning
confidence: 99%
“…The size of complete chloroplast genome sequences range between 107 and 217 kb. Genome size fluctuations could be attributed to; duplication of genes and occurrence of small repeats (Xu et al, 2015), gene loss and/or transfer to other genomes (Stegemann et al, 2003) and the contraction/expansion of the inverted repeats at the four IR/SC junctions (Downie & Jansen, 2015). …”
Section: Introductionmentioning
confidence: 99%